2015
DOI: 10.1294/jes.26.89
|View full text |Cite
|
Sign up to set email alerts
|

Presumed monozygotic twins develop following transfer of an <i>in vitro</i>-produced equine embryo

Abstract: An equine embryo produced by intracytoplasmic sperm injection (ICSI) was trans-cervically transferred to a recipient mare and pregnancy was confirmed via ultrasound examination on days 11, 12 and 15. On days 20 and 22, a single embryonic proper with a heartbeat was observed. On day 29, two embryos proper appeared during ultrasound examination, each possessing a heartbeat. Subsequent examinations on days 35 and 39 revealed continued viability and development of both embryos proper. On day 49, demise of both fet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…We recently reported that a small embryonic vesicle on day 7 after transfer of an IVP embryo was associated with an increased incidence of early embryonic loss . Similar to our findings, all cases of multiple pregnancy after transfer of single IVP (n = 1) and in vivo (n = 6) equine embryo in other reports resulted in either early pregnancy loss or late‐term abortion . Since twin reduction was only attempted in one set of twins, we can only speculate on the likely success of twin reduction.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We recently reported that a small embryonic vesicle on day 7 after transfer of an IVP embryo was associated with an increased incidence of early embryonic loss . Similar to our findings, all cases of multiple pregnancy after transfer of single IVP (n = 1) and in vivo (n = 6) equine embryo in other reports resulted in either early pregnancy loss or late‐term abortion . Since twin reduction was only attempted in one set of twins, we can only speculate on the likely success of twin reduction.…”
Section: Discussionsupporting
confidence: 89%
“…Roberts et al . described series of ultrasound examinations of a twin pregnancy that developed after ICSI that they presumed to be monozygotic. This report expands upon the possibility of monozygotic multiple pregnancy after IVEP by describing the incidence and characteristics of monozygotic twins and triplets after transfer of single frozen‐thawed IVP equine embryos.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monozygotic twins and triplets are reported but are considered very rare (Meadows and others 1995, Govaere and others 2009). Proportionately, more cases have been described after embryo transfer (McCue and others 1998, Sper and others 2012, Roberts and others 2015), which may suggest an association between assisted reproductive techniques and monozygous twins, or it may simply be a factor that they are more appropriately recognised after transfer of a single embryo. Newcombe (2000) reported a review of pregnancy records for over 6000 broodmares over seven years and this suggested that up to 2.6 per cent of twin pregnancies may originate from a single ovulatory follicle.…”
Section: The Origin Of Twinsmentioning
confidence: 99%
“…In humans, MZ twins are born in 0.3 % of all spontaneous livebirths (Hall, 2003). After in vitro procedure and embryo transfer, the emergence of MZ twins is observed more frequently, as shown in species such as horse (Mancill et al, 2011;Roberts et al, 2015), cattle (Kraay et al, 1983;Niemann and Sacher, 1984) and human (Aston et al, 2008;Blickstein et al, 2003).…”
Section: Introductionmentioning
confidence: 99%